2013
DOI: 10.1002/hep.26697
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor CCR6-dependent accumulation of γδ T cells in injured liver restricts hepatic inflammation and fibrosis

Abstract: Chronic liver injury promotes hepatic inflammation, representing a prerequisite for organ fibrosis. We hypothesized a contribution of chemokine receptor CCR6 and its ligand, CCL20, which may regulate migration of T-helper (Th)17, regulatory, and gamma-delta (γδ) T cells. CCR6 and CCL20 expression was intrahepatically up-regulated in patients with chronic liver diseases (n = 50), compared to control liver (n = 5). Immunohistochemistry revealed the periportal accumulation of CCR6+ mononuclear cells and CCL20 ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
147
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 157 publications
(150 citation statements)
references
References 31 publications
1
147
2
Order By: Relevance
“…Moreover, CCL20 induced proinflammatory and profibrogenic effects in cultured primary HSCs. On the other hand, in murine experimental fibrosis, CCL20 favors the recruitment of gamma-delta T cells, limiting inflammation and fibrosis [86].…”
Section: Chemokinesmentioning
confidence: 99%
“…Moreover, CCL20 induced proinflammatory and profibrogenic effects in cultured primary HSCs. On the other hand, in murine experimental fibrosis, CCL20 favors the recruitment of gamma-delta T cells, limiting inflammation and fibrosis [86].…”
Section: Chemokinesmentioning
confidence: 99%
“…In addition, γδ T-cell receptor expressing T-cells (γδ Tcells) restrict hepatic inflammation and fibrosis. During hepatic injury, these cells co-localize with HSC in vivo and promote apoptosis or primary HSC in a cell-cell contact-dependent manner, most likely through activation of the Fas-ligand pathway [34] .…”
Section: Shifting the Hepatic Microenvironment From Inflammation To Rmentioning
confidence: 99%
“…In fact, it has been recently reported that CCR9 is increased in mononuclear cells and activated hepatic stellate cells during liver fibrosis and that CCR9 deficiency reduces liver inflammation in CCl4-treated mice [23]. Similarly, CCR6 has been shown to stay upregulated in CD4 + cells in experimental fibrosis and intrahepatically in patients with chronic liver diseases [24].…”
Section: Discussionmentioning
confidence: 97%